Factors Influencing Consumer Decisions in Choosing Circumcision Service Providers in Malang City: The 7Ps Marketing Mix Approach - Yunus Hani Dewanta; Metta Padmalia; Elia Ardyan (Green Publisher Indonesia, 2025)
The circumcision service industry in Malang City has grown rapidly, with a 46.84% increase in clinics over five years, intensifying competition among providers. Consumer decision-making in elective healthcare services such as circumcision involves factors beyond medical considerations. This study examines the factors influencing consumer choices of circumcision clinics using the 7Ps marketing mix framework. A quantitative approach was employed, distributing questionnaires to 195 parents who used circumcision services for children under 12 during 2023–2024 in Malang. Using purposive sampling, the data were analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM) to assess construct validity and variable relationships. Results show that only four marketing mix elements significantly influenced decisions: price, process, product, and people. Meanwhile, place, promotion, and physical evidence were not significant. This suggests consumers prioritize fair pricing, service quality, efficient procedures, and professional staff over clinic location, advertising, or interior design. The study’s novelty lies in focusing specifically on specialized circumcision clinics within Malang City, a category previously understudied despite its economic relevance. Limitations include a narrow geographic focus and a quantitative design, which may overlook emotional or subjective factors. Future research should expand geographically and incorporate qualitative or mixed methods for deeper insight into consumer motivations.